ACTUALITY AND “UNTIMELINESS” IN THE DISCOURSE ON THE REFUGEE CRISIS THE CASE OF HUNGARY - Zsuzsanna LURCZA (Studia Universitatis Babeș-Bolyai. Philosophia, 2018)
The figure of the refugee and asylum seeker, hidden from the masses, de-humanised, deprived of existence and rights, are in sharp contrast with their representation in the Hungarian mass media and in visual and textual materials of the Hungarian Governmental Information, which constructs a manipulated, extremist and xenophobic, ideologically biased reality. In this sense, the discourse on the refugee crisis has an actual and an untimely form. The first chapter of the paper is an ideology-criticism analysis, aiming at the deconstruction of the ideological subject-construct of the contemporary refugee existence. This analysis focuses on the Hungarian political language used to refer to the European refugee crisis since 2015, primarily the political questionnaire entitled National Consultation on Immigration and Terrorism and the text and poster campaign of the Governmental Information related to it, with references to the later, 2017 Let’s Stop Brussels campaign, 2016 Hungarian Migrant quota referendum, 2017 Soros-plan Consultation, and materials of the information campaign Wirtschaft Zusammen Integrationsinitiativen der Deutschen Wirtschaft in Germany. In the second part, this contemporary constructed form of refugee and asylum seeker existence is paralleled with its untimely discourse.